PENGARUH KEPEMIMPINAN, KOMUNIKASI, DAN TINGKAT PENDIDIKAN TERHADAP PARTISIPASI MASYARAKAT DALAM PENGELOLAAN PLTBM BONDOSULA KECAMATAN LAMBOYA KABUPATEN SUMBA BARAT - Naema Marya Bernadin Woleka; Laurensius P. Sayrani; Agus Susanto (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2024)
The aim of this research is to analyze the influence of leadership, communication and level of education on community participation in the management of PLTBM Bondosula Hamlet, Lamboya District, West Sumba Regency. This research uses a quantitative research approach. The population of this study were residents of the Bondosula community, Lamboya District, West Sumba Regency who were over 17 years old, namely 420 people. The sample for this research was obtained using a simple random sampling technique which was calculated using the Slovin formula, namely 81 people. Data was obtained using a questionnaire and analyzed using multiple linear regression analysis. Community participation plays a role in the social and economic development of a region. Until now, the West Sumba Regency Government has not been fully able to manage the Bondosula PLTBm due to inadequate community participation and other technical problems. To increase the level of participation, it is necessary to understand the influencing factors, including leadership, communication and level of education. The results of the research show that leadership, communication, and level of education influence community participation in the management of PLTBM Bondosula Hamlet, Lamboya District, West Sumba Regency. The aim of this research is to analyze the influence of leadership, communication and level of education on community participation in the management of PLTBM Bondosula Hamlet, Lamboya District, West Sumba Regency. This research uses a quantitative research approach. The population of this study were residents of the Bondosula community, Lamboya District, West Sumba Regency who were over 17 years old, namely 420 people. The sample for this research was obtained using a simple random sampling technique which was calculated using the Slovin formula, namely 81 people. Data was obtained using a questionnaire and analyzed using multiple linear regression analysis. Community participation plays a role in the social and economic development of a region. Until now, the West Sumba Regency Government has not been fully able to manage the Bondosula PLTBm due to inadequate community participation and other technical problems. To increase the level of participation, it is necessary to understand the influencing factors, including leadership, communication and level of education. The results of the research show that leadership, communication, and level of education influence community participation in the management of PLTBM Bondosula Hamlet, Lamboya District, West Sumba Regency.